Cucurbit[7]uril-based fluorene polyrotaxanes. (October 2016) - Farcas, Aurica; Assaf, Khaleel I.; Resmerita, Ana-Maria; Cantin, Sophie; Balan, Mihaela; Aubert, Pierre-Henri; Nau, Werner M.
Graphical Abstract: Highlights: UV–vis provides strong binding affinity of the CB7 towards the neutral dibromofluorene guest. The DFT-optimized structure of1 ·CB7 and3 ·CB7 confirms the presence of the CB7 host molecule. Photophysical properties of3 ·CB7 provide evidence for a diminished aggregation tendency. Abstract: Poly[2, 7-(9, 9-dioctylfluorene)- alt -(2, 7-fluorene/cucurbit[7]uril)] polyrotaxane was synthesized according to Suzuki coupling protocol in DMSO, by reacting 2, 7-dibromofluorene encapsulated into the cucurbit[7]uril (CB7) cavity with 9, 9-dioctylfluorene-2, 7-diboronic acid bis(1, 3-propanediol) ester. The K a value (9.5 × 10 3 M −1 ) indicates that 2, 7-dibromofluorene provides a preferential binding to CB7, which allows the synthesis of a polyrotaxane with a CB7/structural unit ratio of about 1/3 and higher molecular weights. The chemical structure was proven by FTIR and 1 H NMR spectroscopy. The thermal, optical, electrochemical, wetting, and surface morphological properties of the polyrotaxane have been investigated and compared to those of the neat copolymer. The polyrotaxane exhibits an enhancement in the glass transition temperature, blue-shifted absorption by about 11 nm, and a subtle effect on the LUMO energy levels. The fluorescence lifetimes follow a mono-exponential decay with a value of τF = 0.7 ns. The electrochemical band gap of the polyrotaxane (3.39 eV) is smaller than that of the uncomplexed compound. Wetting properties reveal a change in the distribution of the dispersive and polar components of the surface free energy through the CB7 encapsulation. Atomic force microscopy indicated further that the polyrotaxane film is uniformly distributed over the substrate area with a regular consistency and lower roughness parameters.